BTEX in vitro exposure tool using human lung cells: Trips and gains. (June 2015) - Liu, Faye F.; Peng, Cheng; Ng, Jack C.
Highlights: Classical in vitro exposure gives poor repeatability and time course effect data. Mass modeling for hanging drop air exposure method is essential. Higher cell density in the hanging drop air exposure system increases sensitivity. Abstract: Cytotoxicity of benzene, toluene, ethylbenzene and xylenes (BTEX) to human lung cells was explored using three different exposure methods: Method 1 – in normal 96-well plates using DMSO as a carrier vehicle, we exposed (a) human lung carcinoma A549 cells, (b) A549 cells over-expressed with cytochrome P450 2E1 cells, and (c) normal lung fibroblast LL-24 cells to benzene, toluene, ethylbenzene and xylene individually and in a mixture which models car exhaust gases for between 1–88 h. We found that the order of the BTEX potency is benzene < toluene < ethylbenzene =  m- xylene with acute BTEX toxicity to A549 ≈ LL-24 > CYP2E1 over-expressed A549 cells. A significant difference was found between inter-assay responses for all 24 h exposures ( P  < 0.005) suggesting a poor assay repeatability. No sign of potency increase was found from 6 to 72 h exposures. Method 2 – Using sealed vials to expose A549 cells to benzene, toluene and ethylbenzene, we observed a twenty-fold increase in their cytotoxicity, but also with no time-course effect. Method 3 – Using air exposed hanging-drop cell culture, we were able to see both an increase of demonstration of toxicity and a time-course effect from 1 to 12 h exposure. We conclude that exposing cells in sealed and unsealed media using DMSO as a carrier vehicle was not suitable for BTEX exposure studies. Hanging-drop air exposure has more potential. It should be noted that if there are any changes in their exposure matrixes, its exposure mass distribution in cells could differ.